2008
DOI: 10.1016/j.tet.2007.09.089
|View full text |Cite
|
Sign up to set email alerts
|

Aza- and carbo-[3+3] annulations of exo-cyclic vinylogous amides and urethanes. Synthesis of tetrahydroindolizidines and an unexpected formation of hexahydroquinolines

Abstract: [3 + 3] Annulations of exo-cyclic vinylogous amides and urethanes with vinyl iminium salts are described here. We observed an intriguing dichotomy in their reaction pathways. For pyrrolidineand azepane-based vinylogous amides or urethanes, aza-[3 + 3] annulation would dominate to give tetrahydroindolizidines, whereas, unexpectedly, for piperidine-based vinylogous amides or urethanes, carbo-[3 + 3] annulation was the pathway, leading to hexahydroquinolines. The origin for such a contrast is likely associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 90 publications
0
17
0
Order By: Relevance
“…The major diastereomer is formed from an upward rotation of the inward methyl group; downward rotation is apparently disfavoured due to severe close interactions with the metal and its ligands. [144][145][146][147][148][149][150][151][152] In situ generated 1-azatrienes undergo efficient electrocyclization en route to 1,2-dihydropyridines, and chiral subsituents on the azatriene nitrogen or the C-terminus of the triene are effective in controlling the stereochemistry of the electrocyclic process (Scheme 30).…”
Section: Thermal Reactions 4p Electrocyclizations ( P 4 a )mentioning
confidence: 99%
“…The major diastereomer is formed from an upward rotation of the inward methyl group; downward rotation is apparently disfavoured due to severe close interactions with the metal and its ligands. [144][145][146][147][148][149][150][151][152] In situ generated 1-azatrienes undergo efficient electrocyclization en route to 1,2-dihydropyridines, and chiral subsituents on the azatriene nitrogen or the C-terminus of the triene are effective in controlling the stereochemistry of the electrocyclic process (Scheme 30).…”
Section: Thermal Reactions 4p Electrocyclizations ( P 4 a )mentioning
confidence: 99%
“…Another major methodological development in this area was the unveiling of an interesting variant of the carbo -[3 + 3] annulation23 that competes with the aza -[3 + 3] annulation pathway. We observed that annulations of the piperidine-based exocyclic vinylogous urethanes 19 proceeded through an unexpected carbo -[3 + 3] annulation pathway,3,24 leading to hexahydroquinolines 22 [Scheme 6].…”
Section: Introductionmentioning
confidence: 99%
“…6 Although we have developed highly torquoselective electrocyclizations of a chiral auxiliary substituted 1-azatrienes, 7 a more general and practical approach employing chiral enals has yielded diastereoselectivity of 83:17 at best (see aza-electrocyclization of 3a in Scheme 2). 8 9 . Recently, our collaborative efforts to understand the origins of the stereoselectivities of a number of pericyclic reactions 10 have led us to model these stereoselective ring closures computationally.…”
mentioning
confidence: 99%